A Methodological Approach to Process Intensification - Wood, Mark D. (Cranfield University, 2000)
A methodological approach to process intensification (PI) has been developed to aid in the design of intensified chemical processes. Current process development procedures fail to consider if, and how, a chemical process can be intensified, resulting in limited application of PI in the chemicals industry. The PI methodology has been developed to meet these needs, focusing upon the chemical reaction stages of a process. The PI methodology is a paper-based tool, based around a flowsheet known as the framework. Throughout development, the methodology was applied to industrial case studies which revealed considerations that should be included in the methodology and aided in determining its format. Each section of the framework contains checklists and procedures detailing the information required and the decisions to be made by the participants, who should be in a multi-disciplinary team. Examination of chemical reaction kinetics and the effects of mixing upon the reaction are key aspects of the methodology that are normally not examined during process development. Incorporated within the methodology is a PI experimental protocol designed to model PI operation in the laboratory. Mixing theory was reviewed to identify that the protocol approach should be based upon recreating the mixing conditions experienced in a full scale plant within a small scale laboratory stirred vessel. The developed laboratory protocol utilises semi-batch operation in a highly-mixed stirred vessel of 10cm diameter and height with twin pitched-blade turbine impellers. Turbulent energy dissipation rates of 150 W/kg can be achieved in the vessel. Experiments were run, showing that the performance of static mixer reactors can be predicted through the application of the protocol, though future work is required to develop this laboratory protocol approach into a rigorous experimental tool.